Peculiarities of the central mesenteric lymph node of rats of the fi rst month of life in normal conditions and after antenatal antigenic exposure - E. G. Aliyevа (Zaporozhye State Medical University, 2012)
The development of mesenteric lymph node in early postnatal period of ontogenesis in norm and under the infl uence of the intrauterine injection of an antigen - human immunoglobulin was investigated. It is established, that the intrauterine antigen injection provokes the maturation of mesenteric lymph node lymphoid structures and defi nes phased changes in its development.